Students’ Experiences with Learning Environment Affecting English Speaking Ability - Roni Juliansyah; Harjuli Surya Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study purposes to discover students' experiences in dealing with the influence of the learning environment on English speaking ability.  A helpful learning environment is assumed to improve students' speaking abilities, but how students’ experience it in such an environment has not been widely explored. This study uses a qualitative approach with a case study method, through in-depth interviews and observations of a number of students. The results of the study indicate that students who learn in a helpful environment tend to feel more confident and motivated to speak English, while students in less supportive environments face greater challenges in improving their speaking abilities. Based on the findings from interviews, observations, and data analysis, it can be concluded that a supportive learning environment either at campus or in students' social environment plays a main role in improving English abilities. Obstacles like fear of making mistakes in speaking are also challenges to overcome so the learning environment becomes more inclusive and helpful for all students. These findings provide a clear picture of how the learning environment can affect students' English-speaking abilities and how the role of lecturers and other social factors can support this process.